Metastatic prostate adenocarcinoma penis: Case report - Pablo Santiago Caicedo (Revista de la Facultad de Ciencias de la Salud, 2014)
Objective: Describe a case report of a patient with prostatic adenocarcinoma metastatic to penis due to shortage reports of similar cases to perform a literature review. Methods: We identified a case of a patient with prostatic adenocarcinoma, who during de the course of a cystoscopy at Hospital Universitario San Jose (Third-level Public Hospital in Popayan, Colombia) a suspicious nodule of malignancy was observed in the penis. We described the clinical case in order to proceed to a literature search for the discussion. Results: 72-year-old patient diagnosed with prostatic adenocarcinoma Gleason Score 4+5=9, treated with bilateral orchiectomy and a suspicious nodule of malignancy incidentally observed in the penis, currently undergoing palliative care with Karnofsky score of 30 points. Conclusion: cutaneous metastases are rare; indicate longstanding disease and poor prognosis.